Analisis Kebutuhan Air Bersih Dan Distribusi Jaringan PDAM Persemaian Kota Tarakan (Studi Kasus Kecamatan Tarakan Barat) - Asta Asta (Borneo Engineering : Jurnal Teknik Sipil, 2018)
As the population growth in absorb area, there is a significant increase over the function of land water absorb for the needs of investment in a large scale to reduce the absorbing drought during the dry season which able the availability of water sources PDAM especially PDAM at Persemaian in Tarakan City. The analysis method and processing of data in this research was used analysis descriptive, where the data was separated from the number either primary data namely the collection of data from survey in the field and secondary data was the supporting data which was obtained from the relevant institution like BPS and PDAM of Tarakan City then those were separated based on the data characteristic. The data analysis consists of: 1). calculation project of clean water needs at PDAM persemaian in Tarakan City until 2026. 2). The analysis of pipeline distribution network PDAM at Persemaian in Tarakan City by using the program Epanet 2.0. From the calculation of the total population in 2026 was 127.183 soul, and ba sed on the calculation of the average water needs in 2026 was 191,9216 ltr/sec, the maximum needs was 220,7099 lte/sec, so it obtained the needs of clean water until 2026 at the top of 335,8629 ltr/sec. Based on the calculation using epanet 2.0 obtained th e highest pressure score was 9,39 atm (kg/cm 2 ) in junction 131 along 93,96 m and the lowest pressure was 1,10 atm (kg/cm 2 ) in junction 228 along 11,04 m, mean while the highest score of head was 110,83 m in junction 1 and the lowest score of head was 37,00 m in junction 225. Therefore, in 2026 based on the condition of existing pipelines distribution network now, they still can be used in the research location.